POETYCKIE MARZENIE TADEUSZA GAJCEGO W KONFRONTACJI Z TRADYCJĄ ROMANTYCZNĄ I OCENĄ POKOLENIA KOLUMBÓW PRZEZ CZESŁAWA MIŁOSZA I ZBIGNIEWA HERBERTA - Brasse, Rafał (In Gremium. Studies in History, Culture and Politics, 2018)
The poetic dream of Tadeusz Gajcy was not only a means of overcoming the horror and absurdity of the times, but also a way of expressing his personal relationship to the concept of death and sacrifice – growing, after all, out of the experiences of everyday occupation. This subject dominated the creative consciousness of Gajcy and had a decisive influence on the nature of the message contained in his testamental Grom powszedni . The main objective of these reflections is an attempt to find the justification of the motives of his conduct and life choices in the poetry of Tadeusz Gajcy. In the work I distinguished three complementary parts. In the first one I focused on the analysis of poetic images of Gajcy, paying attention to the role of poetic dreams in shaping ethical attitudes. In the second I was preoccupied with the problems of the victim in relation to the romantic tradition of martyrdom as present in the works of the author of Przed odejściem. In the last, and the most comprehensive, part I attempted to confront the poetic message of Tadeusz Gajcy with the assessment of those events and attitudes by Czesław Miłosz. In this part of the work I included also – as important from the perspective of the continuation of the brave attitude – the relationship of Zbigniew Herbert to the life choices of the Generation of Columbuses.